2022
DOI: 10.1371/journal.pone.0278944
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality risk stratification of Asian ACS patients with artificial intelligence algorithm

Abstract: Background Conventional risk score for predicting in-hospital mortality following Acute Coronary Syndrome (ACS) is not catered for Asian patients and requires different types of scoring algorithms for STEMI and NSTEMI patients. Objective To derive a single algorithm using deep learning and machine learning for the prediction and identification of factors associated with in-hospital mortality in Asian patients with ACS and to compare performance to a conventional risk score. Methods The Malaysian National C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to develop and train a machine-learning model for the prediction of in-hospital mortality exclusively for females with ACS. Prior studies have constructed models for the prediction of in-hospital mortality among all ACS patients ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to develop and train a machine-learning model for the prediction of in-hospital mortality exclusively for females with ACS. Prior studies have constructed models for the prediction of in-hospital mortality among all ACS patients ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [ 19 , 49 , 51 ] has shown that features selected by SVM improve model performance when compared to other ML techniques. This led to the prioritization of SVM-ranked features in our feature selection procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its simplicity, NB can perform remarkably well, particularly when the independence assumption is obeyed. The selection of these algorithms was based on prior studies pertaining to mortality associated with cardiovascular disease [13,17,[48][49][50][51]. A combination of random search and manual adjustment was used to fine-tune the hyperparameters of the ML and stacked EL models, ensuring that the models are optimally configured for the task.…”
Section: Development Of Risk Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This predictive model utilizes data from the Korean Acute Myocardial Infarction Registry (KAMIR). Utilizing the National Cardiovascular Disease Database (NCVD) of Malaysia, models that combine DL and ML technologies have also been employed to stratify the in-hospital mortality risk of Asian ACS patients 14 , This further con rms the signi cant value of AI in enhancing the management e ciency of cardiovascular diseases.…”
mentioning
confidence: 99%